FORECASTING MODEL OF VIETNAMESE CONSUMERS’ PURCHASE DECISION OF DOMESTIC APPAREL - Luu, Dung Tien (The European Journal of Applied Economics, 2019)
The study of the determinants of consumer purchase decision of domestic goods is necessary in the context of Vietnams’ international integration in order to support domestic firms to improve their competitiveness. This study aims to analyze the factors influencing Vietnamese consumers’ purchase decision of domestic apparel based on the Binary Logistic regression model. This study uses survey data gathered from 240 consumers in Vietnam in 2019. The research results showed that i) Perceived price, ii) Perceived quality, iii) Consumer ethnocentrism, and iv) Demographic variables (age; the family with a child; the level of education; income; and sex) have significant influences on the consumer purchase decision of domestic apparel in Vietnam.
Keywords: purchase; decision; consumer; Vietnam; perceived quality; perceived pric; domestic apparel; consumer ethnocentrism